PENGARUH KOMPOSISI MEDIUM PERENDAM TERHADAP MASA KESEGARAN BUNGA POTONG KRISAN (Chrysanthemum morifolium R.) - Desi Arisanti; Erma Prihastanti; Endang Kusdiyantini (Jurnal Akademika Biologi, 2013)
Chrysanthemum morifolium is a cut flower with high economic value, however this flower has relatively short freshness period, thus it is necessary to use soaking solution by adding shredded basil leaves extract solution and carrageenan hydrogel material in it. Hydrogel serves as the water provider and energy substrate for respiration process of chrysanthemum. The basil leaves extract works as anti-bacterial and anti-fungal. The soaking is done to extend the freshness period of the chrysanthemums. This study aims to describe the effect ofthe composition of basil leaves extract and carrageenan hydrogel material on soaking medium to the freshness period of chrysanthemum, also to study the microorganism growth on the soaking medium. This research uses Completely Randomize Design on factorial pattern with two factors. First, Hydrogel Concentration (H): without hydrogel, 500 ml of water (H0); 10 g of carrageenan hydrogel, 400 ml of basil solvent (H1); 10 g of carrageenan hydrogel, 500 ml of basil solvent (H2); 10 g of carrageenan hydrogel, 600 ml of basil solvent (H3). Second, basil leaves extract (K): without basil leaves extract, without hydrogel (K0); 125 g/l of basil leaves extract (K1); 250 g/l of basil leaves extract (K2); 375 g/l of basil leaves extract (K3). This research uses 16 treatments 3 replications. The analysis is done by applying ANOVA, followed by Duncan’s test at the significance level of 95%. The research parameter includes the blooming flowers percentage, freshness period of spray chrysanthemum, and the condition of the soaking medium. The findings show that the composition of 400 ml of  250 g/l concentration of basil leaves extract, and 10 g of carrageenan hydrogel can extend the freshness period of chrysanthemum by 12.67 days, and prove that some microorganisms grow in the soaking medium. Keywords: spray chrysanthemums, soaking medium, basil leaves extract, carrageenan hydrogel, freshness period.